Fisheries and trade of seahorses, Hippocampus spp., in southern India - K . R . SALIN, T . M. YOHANNAN and C . MOHANAKUMARAN NAIR (\Fisheries Management and Ecology, 2005, 12, 269-273, 2005)
Seahorses (Hippocampus spp.) are a major commodity fished from the shallow coastal seas of the south coast of India where there is an abundance of sea grasses, sponges and corals. They are in great demand for export as traditional medicines, curios and aquarium fish. Organised fishing and trade of seahorses exists in India along the Palk Bay and Gulf of Mannar coasts. At the Palk Bay coast, seahorses are targeted by divers along with sea cucumbers (Holothuria spp.) and gastropods (e.g. Murex spp., Xancus pyrum Hornell). In the Gulf of Mannar, most of the seahorses are landed as bycatch of shrimp trawling. Seahorses are also fished from Kerala as a bycatch of trawling, although no organised fishery and trade exists. Five species of seahorses were identified from the Palk Bay coast, whereas only two species were obtained from Kerala. Most seahorses from India are exported to Singapore, Hong Kong, Malaysia and the United Arab Emirates. The volume of dried seahorse trade from India was estimated to be 9.75 t as derived from catch data in 2001, which was much higher than official statistics of 4.34 t during 2001-2002, suggesting the major part of the exports might be through non-conventional means and goes undeclared. Some aspects of the impact of large-scale fishing and trade on conservation of these seahorses are discussed.